Potential Transmission of Filariasis for Pregnant Women in Subdistrict Muara Pawan, Ketapang District, Province of West Kalimantan - Nuhdi Arfarisy (Universitas Airlangga, 2017)
Filariasis (elephantiasis) is a contagious disease caused by filarial worms that lives in the channel and lymph nodes (lymph) in the human body. The disease in transmitted through mosquito bites. Sub District Muara Pawan in Ketapang district is endemic region of filariasis so than Bulk Drug Prevention (Diethyl Citrate Carbamazine) against the whole of society in needed except in pregnant women because of the side effects of these drugs for pregnant women and fetus. Based on the preliminary survey and information from Ketapang District Office there were a few factors that play a role in the transmission, that were environmental factor and social behavior. This research was a descriptive cross sectional design conducted at Sub District Muara Pawan Ketapang District. Data were collected through observation and interviews. The research objective was a determine the potential transmission of filariasis in pregnant at Sub District Muara Pawan Ketapang District in West Kalimantan. Result showed that finger blood test results conducted on 53 samples of pregnant women did not find microfilaria in the blood. The results of the identification of mosquitoes are found is the dominant mosquito species Anopheles letifer. Results of laboratory tests were conducted by B2P2VRP Salatiga to 399 mosquitoes are not found filarial worms in the body of the mosquito. There are five variables that have the potential for transmission of filariasis in pregnant women in Puskesmas Tanjung Pura Sub Muara Pawan namely the level of knowledge is less (66.0%), there is mosquito habitat (75.5%), there is a place resting mosquitoes (71.7%), the habit of not using anti-mosquito drugs (66.0%), the habit of not using a closed clothes at home (73.6%). The conclusion of this study is the environmental factors and poor public behavior turned out to be very influential on the potential transmission of filariasis incidence in pregnant women.